Prognostic value of low-level MRD in adult acute lymphoblastic leukemia detected by low- and high-throughput methods - Kotrová, Michaela; Koopmann, Johannes; Trautmann, Heiko; Alakel, Nael; Beck, Joachim; Nachtkamp, Kathrin; Steffen, Björn; Raffel, Simon; Viardot, Andreas; Wethmar, Klaus; Darzentas, Nikos; Baldus, Claudia D.; et al. (Blood advances, 2022)
Persistence of minimal residual disease (MRD) after induction/consolidation therapy in acute lymphoblastic leukemia is the leading cause of relapse. The GMALL 07/2003 study used MRD detection by real-time quantitative polymerase chain reaction of clonal immune gene rearrangements with 1 × 10−4 as discriminating cutoff: levels ≥1 × 10−4 define molecular failure and MRD-negativity with an assay sensitivity of at least 1 × 10−4 defining complete molecular response. The clinical relevance of MRD results not fitting into these categories is unclear and termed “molecular not evaluable” (MolNE) toward MRD-based treatment decisions. Within the GMALL 07/03 study, 1019 consecutive bone marrow samples after first consolidation were evaluated for MRD. Patients with complete molecular response had significantly better outcome (5-year overall survival [OS] = 85% ± 2%, n = 603; 5-year disease-free survival [DFS] = 73% ± 2%, n = 599) compared with patients with molecular failure (5-year OS = 40% ± 3%, n = 238; 5-year DFS = 29% ± 3%, n = 208), with patients with MolNE in between (5-year OS = 66% ± 4%; 5-year DFS = 52% ± 4%, n = 178). Of MolNE samples reanalyzed using next-generation sequencing (NGS), patients with undetectable NGS-MRD (n = 44; 5-year OS = 88% ± 5%, 5-year DFS = 70% ± 7%) had significantly better outcome than those with positive NGS-MRD (n = 42; 5-year OS = 37% ± 8%; 5-year DFS = 33% ± 8%). MolNE MRD results not just are borderline values with questionable relevance but also form an intermediate-risk group, assignment of which can be further improved by NGS.
Gesehen am 25.08.2022